Comparative superovulation outcomes across estrous phases using PMSG-hCG and rFSH-rhCG in mice - Maula, Yogi Nikmatul; Salsabila, Cyntia Bella; Pristihadi, Diah Nugrahani; Haq, Noer Muhammad Dliyaul; Boediono, Arief (Current Biomedicine, 2025)
Background Enhancing stimulation efficiency in mice supports the application of assisted reproductive technologies (ART) for species conservation. Objective This study compared the stimulatory potential of two ART-supporting hormone protocols: the conventional PMSG-hCG combination and recombinant gonadotropins (rFSH-rhCG), a newer generation produced by genetic engineering. Methods Sixty-three female mice from four distinct estrous phases were used in this study. Both hormone regimens, with FSH- and LH-like activities, were administered sequentially between 4:00 and 5:00 pm, at a 47–48 h interval. Stimulation success was evaluated based on the proportion of females showing a positive response and the number of oocytes retrieved. Results The diestrus phase yielded the highest response for both treatments. Approximately 60% of the females responded to PMSG-hCG, and 80% responded to recombinant hormones. The number of oocytes recovered reached 239 in the PMSG-hCG group and 137 in the recombinant group. Interestingly, recombinant hormone administration during estrus induced ovulation of 400 oocytes; however, the efficiency ratio was lower than that during diestrus (30.8 vs 34.3). Conclusion Both PMSG-hCG and recombinant gonadotropins effectively stimulate ovulation. The diestrus phase provides the most consistent results; therefore, diestrus is recommended as the optimal stage for superovulation protocols in mice.